Slovenska podjetja in okoljski vidiki poslovanja: Slovenski podjetniški observatorij 2014 - Rebernik, Miroslav; Močnik, Dijana; Bradač Hojnik, Barbara (University of Maribor Press, 2015)
Slovenian Companies and Environmental aspects of Business : Slovenian Entrepreneurship Observatory 2014. In this monograph, we first analysed all the companies and entrepreneurs in Slovenia in 2013 and then, for 2011, we compared the critical data for companies from EU-28 and Slovenia in the non-financial business sector (activities of industry, trade and services). In Slovenia in 2013, 61,312 companies (almost 3% more than in the previous year) and 69,626 entrepreneurs, —totalling 130,938 enterprises— employed almost 522,000 people. More than one fourth of enterprises in the non-financial business economy in EU-28 in 2011 operated in distributive trades (motor trades, wholesale trade and retail trade). The second part of the monograph analyses environmental aspects of business operations. The development of innovation in its broadest sense is always associated with entrepreneurial activities; therefore, these are closely related concepts. In this chapter, we expose the variety of different aspects and manifestations of both concepts and their interconnections. We provide information on the state of environmental entrepreneurship and eco-innovation as well as their characteristics in Slovenia compared with other European countries.